Structure of self-rated health among the oldest old: Analyses in the total population and those living with dementia - Inna Lisko; Timo Törmäkangas; Marja Jylhä (Elsevier, 2020)
No previous study has explored the structure of self-rated health (SRH), a measure holding strong predictive value for future health events, in the oldest old or in individuals with dementia. The aim was to construct a structural equation model of SRH for oldest old in general and for oldest old with dementia, and to explore direct and indirect associations between health-related factors and SRH. Cross-sectional data from the Vitality 90+, a population-based study in the city of Tampere, Finland, was used. Data were gathered by a mailed questionnaire in 2014. Altogether 1299 nonagenarians, of which 408 had self-reported dementia or cognitive decline, were included. Structural equation models were constructed for all participants and separately for participants with dementia. Diseases (heart disease, stroke, diabetes, arthritis, hip fracture, cancer and dementia for the model for all), dizziness, hearing, vision, mobility, activities of daily living, fatigue, depression and SRH were included in the models. Among all participants, fatigue, depression, problems in mobility, dizziness, deficits in vision and heart disease were directly associated with poor SRH. Among participants with dementia, only fatigue, dizziness and deficits in vision were directly associated with poor SRH. Among all participants, dementia and arthritis were indirectly associated with poor SRH through problems in mobility, depression and fatigue. Among the oldest old, the effects of diseases on SRH were mainly manifested through the consequences of diseases, namely fatigue, dizziness, deficits in vision and problems in mobility. Depression has an important direct and indirect role, and dementia and arthritis an important indirect role in the structure of SRH. Dementia weakens many of the direct and indirect associations for SRH.